Power flow control for power and voltage management in future smart energy communities - Fazeli, A; Sumner, M.; Christopher, Edward; Johnson, Christopher Mark (2014)
The Community Power Flow Control (CPFC) Algorithm has been proposed as a technique for managing electrical power and energy within small communities. The CPFC manages the resources in the community (DSM, energy storage, RES) in order to control the community’s instantaneous power flow according to a target set by a higher-level management system. This paper investigates the capability of the CPFC to manage local distribution voltage levels. The power flow data for a community has been used together with transformer and cable impedance models to demonstrate the variation of the distribution voltage in a community with significant penetration of PV and EV. The CPFC is shown to manage the voltage levels along a feeder within the statutory limits, even when there is significant export.